Coefficient of static friction of palm kernel shell on selected structural surfaces (2000)
An experiment was conducted to measure the static coefficient of friction of palm kernel shell (PKS) on plywood, galvanized iron and glass. The results of the test showed that the coefficient of static friction of PKS increases with moisture content irrespective of the surface employed. The .values of coefficient of static friction obtained varied from 0.42 to 0.75 on plywood, 0.34 to 0.62 on galvanized iron and 0.32 to 0.56 on glass for moisture contents ranging from bone dry to 18.4% wet basis. This implies that PKS is most resistant to flow on plywood and least on glass. A statistical analysis showed that these variations with structural surfaces were Significant. Further similar work using the cracked palm kernel is recommended.